The evolution of war: theory and controversy. Issue 1 (29th October 2015) - Lopez, Anthony C.
Abstract : The use of evolutionary theory for explaining human warfare is an expanding area of inquiry, but it remains obstructed by two important hurdles. One is that there is ambiguity about how to build an evolutionary theory of human warfare. The second is that there is ambiguity about how to interpret existing evidence relating to the evolution of warfare. This paper addresses these problems, first by outlining an evolutionary theory of human warfare, and second by investigating the veracity of four common claims made against the use of evolutionary theory for explaining warfare. These claims are: (1) ancestral warfare was not frequent or intense enough to have selected for psychological adaptations in humans for warfare; (2) the existence of peaceful societies falsifies the claim that humans possess adaptations for fighting; (3) if psychological adaptations for warfare exist, then war is an inevitable and universal component of the human condition; (4) modern warfare and international politics is so qualitatively different from ancestral politics that any adaptations for the latter are inoperative or irrelevant today. By outlining an evolutionary theory of war and clarifying key misunderstandings regarding this approach, international relations scholars are better positioned to understand, engage, and contribute to emerging scholarship on human warfare across the social and evolutionary sciences.